2002
DOI: 10.1177/153537020222701111
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Cyclic GMP Signaling Pathway in the Regulation of Rabbit Clitoral Cavernosum Tone1

Abstract: We investigated the role of nitric oxide (NO)-guanosine 3′,5′-cyclic monophosphate (cGMP) signaling in the regulation of rabbit clitoral cavernosum (CC) tone. Tension measurements, reverse transcriptase-polymerase chain reaction (RT-PCR), Western blotting, and NADPH-diaphorase staining were performed in CC. In the precontracted CC strips with phenylephrine (10–5 M), acetylcholine (ACh) relaxed, dependent on dosage. Pretreatment with atropine, Nω nitro-l-arginine-methyl ester (NAME) or 1H-[1,2,4]oxadiazolo[4,3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Nitrergic nerves (4) and, more specifically, NO and cGMP (29), have been shown to cause relaxation in rabbit clitoral corpus cavernosum. These meticulous studies showed that EFS induces nitrergic relaxation responses by a mechanism that is inhibited by TTX, ODQ, and L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrergic nerves (4) and, more specifically, NO and cGMP (29), have been shown to cause relaxation in rabbit clitoral corpus cavernosum. These meticulous studies showed that EFS induces nitrergic relaxation responses by a mechanism that is inhibited by TTX, ODQ, and L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the NO/cGMP system in clitoral erection is further indicated by in vitro animal experiments. In rabbits, clitoral corpus cavernosum inhibition of NOS dramatically abolishes electrically stimulated relaxation, whereas sildenafil augments the relaxation [27,62,63]. In the human clitoral tissue, sildenafil has been demonstrated to inhibit PDE5 [64], and immunohistochemical studies have identified NOS immunoreactive nerve bundles within the glans and corpora cavernosa of the clitoris [65].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Both the vagina and clitoris have been shown to be abundantly innervated by NO-producing neurons [17,18]. During stimulation at the level of the genitalia, NO has been suggested to mediate, at least in part, smooth muscle relaxation via a cyclic guanosine monophosphate-dependent mechanism [19].…”
Section: Introductionmentioning
confidence: 99%
“…While the physiology of a female sexual response has not yet been fully elucidated, evidence to date suggests that nitric oxide (NO) plays a major role, at least in the physiological component of the response [15,16]. Both the vagina and clitoris have been shown to be abundantly innervated by NO-producing neurons [17,18]. During stimulation at the level of the genitalia, NO has been suggested to mediate, at least in part, smooth muscle relaxation via a cyclic guanosine monophosphate-dependent mechanism [19].…”
Section: Introductionmentioning
confidence: 99%